Design and Operation Strategy for a Grid Connected Micro Power System - Okundamiya, Michael Stephen; Ibharunujele, Solomon O. (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2019)
The growing demand for a sustainable power system is motivating worldwide interest in alternative technology. The renewable sources are capable of supplying the required energy but are intermittent and location dependent. A micro power system, if optimally designed can be more reliable and cost effective than a single power source. The overall aim of this paper is the design and operation strategy for a grid connected micro power system for reliable and cost effective energy utilisation. The designed micro power system, is made up of three power sources (solar photovoltaic, grid and fossil-fuelled generator), and utilises a microcontroller based system to reliably organise the flow of the hybrid power mix from different sources and battery bank in a costeffective manner. The microcontroller was programmed to monitor the DC voltage levels of the battery bank to decide which source powers the load. The results showed that the developed strategy yielded grid energy savings of 66.7%, reliability enhancement of 6.1% and reduction of pollutant emission by 36.7% compared to the conventional strategy. The high energy saving as well as improved power supply reliability of the developed strategy has become increasingly necessary especially in the face of exorbitant power supply rates of the various electric power distribution companies in Nigeria. Moreover, the implementation of the developed operation strategy can make the ecosystem more friendly and clean.